DINAMIKA RUANG BERBASIS GENDER, KELAYAKAN HUNI, DAN KEBERLANJUTAN DALAM TRANSFORMASI ARSITEKTUR TRADISIONAL BALI (Jurnal Arsitektur ARCADE, 2026)
The development of tourism in Bali has transformed traditional houses, courtyards, and ritual spaces into environments that serve not only domestic life but also economic activities. Houses and courtyards are now utilized as homestays, culinary production areas, tourism service facilities, and venues for cultural activities. Many studies have interpreted these transformations as manifestations of cultural and economic sustainability. However, discussions concerning gendered spatial dynamics and their implications for habitability remain limited. This article synthesizes the literature on the relationships among gendered space, habitability, and sustainability in the transformation of traditional Balinese architecture. The study employs a Systematic Literature Review (SLR) of 20 national and international journal articles. The selected literature was analyzed thematically to examine the interconnections between spatial transformation, gender-based division of labor, habitability, and sustainability. The findings indicate that the sustainability of Bali’s tourism sector is substantially supported by women’s labor within domestic and ritual spaces. While these roles contribute to the preservation of cultural practices and the strengthening of household economies, they may also reinforce gendered spatial divisions and reduce the quality of women’s lived experiences within the home environment. This article argues that the sustainability of traditional Balinese architecture should not be assessed solely through building preservation, cultural continuity, or economic growth. The experiences of women as primary users of productive domestic spaces must also be recognized as a critical component in evaluating habitability and the broader sustainability of the built environment.